Superficial surgical site infections: A comparative study between elective and emergency gastrointestinal surgeries in children - Adil, Syed Abdul; Alam, Md Mahbubul; Majumder, Partha Sarathy; Hasina, Kaniz; Hossain, Tahmina (Journal of Paediatric Surgeons of Bangladesh, 2019)
Background: Surgical site infections (SSIs) are an important cause of healthcare-associated infections. They complicate the postoperative course of a significant proportion of general abdominal surgical patients and are associated with considerable morbidity and mortality. Risks associated with SSIs are related to both host and perioperative factors. Although intrinsic factors in patients - such as age, underlying illness and site of the procedure - increase the risk, the quality of care delivered during the perioperative period is critical to preventing SSI. The aim and objective of this study was to compare the incidence (percentage) of superficial surgical site infections in elective and emergency gastrointestinal surgeries. Method: In this comparative study, a total number of 60 cases were taken purposively from January, 2015 to December, 2016 in the Department of Pediatric Surgery, Dhaka Medical College Hospital, Dhaka. All the patients, fulfilling the inclusion criteria, were enrolled for emergency gastrointestinal surgery (Group A) and elective gastrointestinal surgery (Group B). For assessing development of SSIs in post operative patients and evaluating the outcome of emergency gastrointestinal surgery, comparison was made with the patients undergoing elective gastrointestinal surgery. ASEPSIS wound scoring method for assessment of wound infections was used during postoperative period. Result: In this study, 20 (66.6%) patients were male in emergency operative group (group A) and 16 (53.3%) patients were male in elective operative group (group B). Age range was 19 days to 12 years in emergency operative group and 10 months to 11 years in elective operative group. In group A out of 30 patients, 6 developed wound infection (20 %) and in group B out of 30 patients, 2 developed wound infection (6.67%). Chi-square test revealed a p value of 0.74 which was > 0.05. So the difference was not significant. Total 5 cases had growth of microorganisms in wound swab in group A and 1 case had growth in group B. Among 5 cases of group A, Staphylococcus aureus, Escherichia coli and Pseudomonus aeruginosa observed in 1, 3, 1 cases respectively. Only 1 case of Escherichia coli was observed in group B. Conclusion: There is no statistical difference in superficial surgical site infections between elective and emergency gastrointestinal surgeries in this study Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (2): 58-62